2023
DOI: 10.1021/acs.molpharmaceut.3c00059
|View full text |Cite
|
Sign up to set email alerts
|

Switch between Cocrystal and Coamorphous Forms Depending on Thermal Modulation of Hot-Melt Extrusion

Abstract: Cocrystal (CC) and coamorphous (CM) techniques have become green technologies to improve the solubility and bioavailability of water-soluble drugs. In this study, hot-melt extrusion (HME) was employed to produce CC and CM formulations of indomethacin (IMC) and nicotinamide (NIC) due to its advantages like solvent-free and large-scale manufacturing. Interestingly, for the first time, IMC−NIC CC and CM were selectively prepared depending on the barrel temperatures of HME at a constant screw speed of 20 rpm and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…It was also proven that, using the hot melt extrusion method, it was possible to adapt the synthesis conditions in such a way that the obtained product will be either a co-crystal or a co-amorphous solid. For instance, Zhang, Qian, Heng et al found that in case of indomethacin (IMC) and nicotinamide (NIC), the temperature 105–120 °C allowed a co-crystal to be obtained, whereas the temperature 125–150 °C provided a co-amorphous solid dispersion . The authors concluded that at low temperatures, the system had high viscosity and slow molecular diffusion, which resulted in a system with low diffusivity and high homogeneity that favored the formation of strong interactions.…”
Section: Co-crystallization and Co-amorphization As Strategies For Im...mentioning
confidence: 75%
“…It was also proven that, using the hot melt extrusion method, it was possible to adapt the synthesis conditions in such a way that the obtained product will be either a co-crystal or a co-amorphous solid. For instance, Zhang, Qian, Heng et al found that in case of indomethacin (IMC) and nicotinamide (NIC), the temperature 105–120 °C allowed a co-crystal to be obtained, whereas the temperature 125–150 °C provided a co-amorphous solid dispersion . The authors concluded that at low temperatures, the system had high viscosity and slow molecular diffusion, which resulted in a system with low diffusivity and high homogeneity that favored the formation of strong interactions.…”
Section: Co-crystallization and Co-amorphization As Strategies For Im...mentioning
confidence: 75%